Transliteration of Latin Letters to Bali Characters Based on Unicode for Mobile Devices using Finite State Automata and Levenshtein Distance - Sandhiyasa, I Made Subrata; Pande, Ni Kadek Nita Noviani; Fibriyanthini, Luh (Sinkron : jurnal dan penelitian teknik informatika, 2024)
The preservation of Balinese script writing has been pursued by the local government with the issuance of the Bali Province Regional Regulation Number 1 of 2018 concerning Balinese Language, Script, and Literature. However, the use of Balinese script in daily life is declining, especially among generation Z, most of whom find Balinese language difficult to use and have never been taught it. Technological advances, particularly smartphone technology, can play an important role in shaping generation Z's habits, values, and social interaction patterns. This research uses the Finite State Automata (FSA) method to convert Latin letters to the Balinese script Unicode standard, following the Balinese script writing rules. FSA governs transliteration behavior by using the working principles of State, Event, and Action. Besides transliterating sentences typed by users, the application produced by this research also displays Balinese script words related to the words typed by users using the Levenshtein Distance method. The ‘related words’ feature allows users to know more about Balinese script than just the typed word. From the test results conducted through two different test cases, the first test case tested the application's ability to transliterate words/sentences typed by users without selecting words from the application's suggestions. The results showed that of the 50 words tested, 39 were correctly transliterated. The second test case tested the app's ability when the user selects a word from the suggestions given by the app. The result shows that out of 50 words tested, 43 transliteration data are correct, with the total accuracy of both test cases being 82%.